2012
DOI: 10.1186/1471-2210-12-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel olanzapine analogues presenting a reduced H1 receptor affinity and retained 5HT2A/D2 binding affinity ratio

Abstract: BackgroundOlanzapine is an atypical antipsychotic drug with high clinical efficacy, but which can cause severe weight gain and metabolic disorders in treated patients. Blockade of the histamine 1 (H1) receptors is believed to play a crucial role in olanzapine induced weight gain, whereas the therapeutic effects of this drug are mainly attributed to its favourable serotoninergic 2A and dopamine 2 (5HT2A/D2) receptor binding affinity ratios.ResultsWe have synthesized novel olanzapine analogues 8a and 8b together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…This study supports the potential role of H 1 receptor affinity in antipsychotic-induced weight gain and fat deposition. As shown in our previous report [27] , OlzEt and OlzHomo have a lower affinity for binding to the H 1 receptors ( K i = 1.95, and K i = 13.63, respectively) compared to that of Olz ( K i = 0.13). Therefore, the pronouced antagonism of OlzEt and OlzHomo at the H 1 receptors may be responsible for their significantly attenuated propensity to induce weight gain and metabolic dysfunction, which are associated with Olz treatment.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…This study supports the potential role of H 1 receptor affinity in antipsychotic-induced weight gain and fat deposition. As shown in our previous report [27] , OlzEt and OlzHomo have a lower affinity for binding to the H 1 receptors ( K i = 1.95, and K i = 13.63, respectively) compared to that of Olz ( K i = 0.13). Therefore, the pronouced antagonism of OlzEt and OlzHomo at the H 1 receptors may be responsible for their significantly attenuated propensity to induce weight gain and metabolic dysfunction, which are associated with Olz treatment.…”
Section: Discussionsupporting
confidence: 62%
“…This effect may be prevented by 5HT 2A antagonism by Olz at the level of motor pathways in the spinal cord or in the brain [61] . In our previous study [27] , OlzEt showed a similar affinity as Olz for blocking the D 2 and 5HT 2A receptors in the striatum and prefrontal cortex respectively, which may partly explain the way in which OlzEt inhibits the PCP-induced behaviours in vivo . On the other hand, OlzHomo demonstrated a lower affinity for blocking these two receptors, which may contribute to its lack of efficacy for alleviating the PCP-induced hyperactivity.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Olanzapine (OZ), an antipsychotic drug for treating brain diseases, was apt to be pumped out by P-gp in blood-brain barrier (BBB) and metabolized by first-pass effect, which suffer9ed great loss before reaching the desired sites and led to low brain permeability (Altamura et al, 2003;Srivastava & Ketter, 2011;Jafari et al, 2012). Based on the unique physical contact of nasal cavity and cranial cavity in the anatomy, nasal mucosal delivery could facilitate drugs across BBB conveniently and effectively by avoiding first-pass metabolism, bypassing efflux of P-gp and reducing the side effects.…”
Section: Mms Strategy For Nasal Drug Deliverymentioning
confidence: 99%
“…Olanzapine (OZ) is a thioeno benzodiazepine class second-generation or atypical antipsychotic that selectively binds to central dopamine D2 and serotonin (5-HT2c) receptors used for the treatment of schizophrenia and bipolar disorder [10,11]. It has poor bioavailability due to hepatic first-pass metabolism and low permeability into the brain due to efflux by P-glycoproteins.…”
Section: Introductionmentioning
confidence: 99%